Master of Arts in Project Planning and Management (MAPPM) - Kabale University (Kabale University, 2022)
The programme aims at providing participants with knowledge and skills necessary for effective performance in the role of project manager. It adopts a generic approach to project management and is designed for projects in construction and engineering, events management, research and development, community services, trade, tourism and agricultural projects. The programme consists of 15 compulsory taught courses while the second part will involve a project inform of a Dissertation Writing.t provides participants with the opportunity to study project planning and management at a broader and advanced level. Special emphasis is placed on both the practical and theoretical aspects of the discipline. The course is suitable for all people working in all organisations specifically Public Service, NGOs, and Private Sector Organisations.